Caribbean Report 03-02-1989 - Whitehorne, Pat (anchor); Norton, Michael (correspondent); O'Shaughnessy, Hugh (correspondent); Jackson, Grace (interviewee); Ottey, Merlene (interviewee); Saunders, Nicholas (interviewee) (The British Broadcasting Corporation, 1989)
A document leakes by the Haitian Ministry of Information that warns of a peasant insurrection leads to a wave of protests and demonstrations. An investigation commission is setup by President Prosper Avril to verify the validity of the document. Many Haitians feels that the government may use the opportunity to stifle dissent to its administration. British journalist, Hugh O'Shaughnessy speaks out on corruption, crime and maladministration in the tiny island of Saint Martin. Racial upsets are particularly disturbing in his interview. Interviews are also held with Jamaican athletes Grace Jackson and Merlene Ottey, and Bermudian athlete, Nicholas Saunders who are invited to Britain to give some tough competition to British athletes. The program ends with a review of Caribbean news in the British press for the past week and includes comments on the recently concluded ACP/EEC meeting in Barbados, elections in Jamaica and Cuban leader, Fidel Castro refusal to re-patriate 24,000 Cuban from Angola who are stricken with AIDS.
1. Headlines: Allegations of an imminent peasant uprising in Haiti; a journalist report of chaos in the tiny island of Saint Martin; and Caribbean stars in track and field are invited to Britain to give British athletes some tough competition (00:00-00:38)
2. A document leaks by the Haitian Ministry of Information that warns of peasant insurrection leads to a wave of protests and demonstrations (00:39-03:52)
3. Interview with British journalist, Hugh O'Shaughnessy on corruption, crime and maladministration in Saint Martin (03:53-06:36)
4. Financial News (06:37-07:35)
Keywords: Peasant uprising -- Haiti.; Insurgency -- Haiti.; Corruption -- Saint Martin.; Crime -- Saint Martin.; Political corruption -- Saint Martin.; Saint Martin -- Race relations.; Track and field athletes -- Jamaica.; Jumping -- Bermuda.; Sports -- Caribbean Area.; Track and field for women -- Jamaica.; AIDS (Disease) -- Cuba.; Elections -- Jamaica.; ACP; EEC